The Impact of Estrogen and Estrogen-Like Molecules in Neurogenesis and Neurodegeneration: Beneficial or Harmful? - Bustamante-Barrientos, Felipe A.; Méndez-Ruette, Maxs; Ortloff, Alexander; Luz-Crawford, Patricia; Rivera, Francisco J.; Figueroa, Carlos D.; Molina, Luis; Bátiz, Luis Federico (Frontiers in Cellular Neuroscience, 2021)
Estrogens and estrogen-like molecules can modify the biology of several cell types. Estrogen receptors alpha (ERα) and beta (ERβ) belong to the so-called classical family of estrogen receptors, while the G protein-coupled estrogen receptor 1 (GPER-1) represents a non-classical estrogen receptor mainly located in the plasma membrane. As estrogen receptors are ubiquitously distributed, they can modulate cell proliferation, differentiation, and survival in several tissues and organs, including the central nervous system (CNS). Estrogens can exert neuroprotective roles by acting as anti-oxidants, promoting DNA repair, inducing the expression of growth factors, and modulating cerebral blood flow. Additionally, estrogen-dependent signaling pathways are involved in regulating the balance between proliferation and differentiation of neural stem/progenitor cells (NSPCs), thus influencing neurogenic processes. Since several estrogen-based therapies are used nowadays and estrogen-like molecules, including phytoestrogens and xenoestrogens, are omnipresent in our environment, estrogen-dependent changes in cell biology and tissue homeostasis have gained attention in human health and disease. This article provides a comprehensive literature review on the current knowledge of estrogen and estrogen-like molecules and their impact on cell survival and neurodegeneration, as well as their role in NSPCs proliferation/differentiation balance and neurogenesis.